2008
DOI: 10.1128/iai.00956-07
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Diversity among Escherichia coli O157:H7 Isolates and Identification of Genes Linked to Human Infections

Abstract: An Escherichia coli oligonucleotide microarray based on three sequenced genomes was validated for comparative genomic microarray hybridization and used to study the diversity of E. coli O157 isolates from human infections and food and animal sources. Among 26 test strains, 24 (including both Shiga toxin [Stx]-positive and -negative strains) were found to be related to the two sequenced E. coli O157:H7 strains, EDL933 and Sakai. However, these strains showed much greater genetic diversity than those reported pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
25
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(26 citation statements)
references
References 47 publications
1
25
0
Order By: Relevance
“…This data suggest that those panel of virulence factors might be essential for the survival of STEC O157 in a host organism and causing the infection. These data are in agreement with the results of other researchers (Wu et al, 2008;Söderlund et al, 2010;Bugarel et al, 2011). They confirmed that the panel of genetic determinants of virulence in the STEC O157 strains genomes are highly typical for this serotype.…”
Section: Discussionsupporting
confidence: 94%
“…This data suggest that those panel of virulence factors might be essential for the survival of STEC O157 in a host organism and causing the infection. These data are in agreement with the results of other researchers (Wu et al, 2008;Söderlund et al, 2010;Bugarel et al, 2011). They confirmed that the panel of genetic determinants of virulence in the STEC O157 strains genomes are highly typical for this serotype.…”
Section: Discussionsupporting
confidence: 94%
“…To further explore genetic diversity within serotype O55:H7, we performed pulsed-field gel electrophoresis (PFGE) and multilocus variable-number tandem repeat analysis (MLVA) on strain RM12579 and 14 other E. coli O55:H7 isolates from around the world and across 51 years of time (Table 1; of five isolates (not including RM12579) shared a similar PFGE pattern using both XbaI and BlnI enzymes, and because this subgroup of five isolates included the reference strain DEC5B (59,71), it is referred to in this paper as the DEC5B subgroup. In order to determine the prevalence of O157:H7 virulence factors within strains of the O55:H7 serotype, we tested a panel of genes, including T3SS effectors and stx, from among those currently under evaluation as markers for virulence (3,74). For comparison, the earliest documented O157:H7 isolate, E. coli O157:H7 strain 2886-75, was tested for the presence of these virulence genes.…”
Section: Resultsmentioning
confidence: 99%
“…The latter serotype has been established as a recent precursor to the virulent enterohemorrhagic E. coli (EHEC) serotype O157:H7 (18,71), which can cause disease in all age groups. Extensive analysis of the diversity of the O157:H7 serotype has provided insight into its continued evolution (15,34,42,75,76) and has led to a search to define genetic properties that could identify more virulent strains of related O157:H7, nonmotile O157, and non-O157 EHEC (3,4,5,8,32,63,74).…”
mentioning
confidence: 99%
“…These method [22] was used to determine susceptibility of studies of the somatic antigens of avian pathogenic E. the isolated APEC to some antibiotics of human and coli have also shown that many strains are untypable veterinary significance on Mueller Hinton agar. Ten similar genetic diversity within [18] and across [19] antimicrobial discs were used at the following serotypes. As APEC share not only identical serotypes concentrations: ciprofloxacin (10µg), streptomycin with human pathogens but also specific virulence (30µg), trimethoprim + sulphametoxazole (30 µg), factors and their zoonotic potential which are under ampicillin (30 µg), oxfloxacin (10 µg), gentamycin consideration [5].…”
Section: Introductionmentioning
confidence: 99%